Removal of tetracycline antibiotic from aqueous solution using biosorbent - Tunc, Muslun Sara; Hanay, Ozge (Elsevier Science Inc, 2022)
As the accumulation of antibiotics has led to increasingly serious environmental pollution problems, many studies have revealed that the adsorption method can be used to efficiently and easily remove residual antibiotics in water with low cost and high efficiency. Chitin being a biosorbent has recently received attention as a new type of adsorption material. The tetracycline (TC) adsorption by chitin was studied through characterization and analysis of chitin and as a function of solution pH, adsorbent dosage, temperature and initial TC concentration. The highest TC adsorption capacity was determined as 7.08 mg/ g for initial TC concentration of 80 mg/L at pH 7 and 55 degrees C. The adsorption process obeyed the pseudo-second- order kinetic model and Freundlich and DubininRadushkevich adsorption isotherm models. TC adsorption onto chitin was also endothermic and spontaneous. The adsorption of TC by chitin was primarily controlled by physical adsorption and chemical adsorption including pore filling, hydrogen bonding and weak electrostatic interaction.
Keywords: Adsorption kinetics; Biosorbent; Chitin; Tetracycline; Thermodynamic